2004
DOI: 10.22621/cfn.v118i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Winter Habitat Use by Wolves, <em>Canis lupus</em>, in Relation to Forest Harvesting in West-central Alberta

Abstract: Forested landscapes in west-central Alberta are facing increased pressures from forest harvesting and other land-use activities, which may alter the movements and distribution of Wolves and ungulates. Information on habitat use by Wolves in logged forests is scarce, potentially limiting effective land-use planning in the boreal forest. Nine Wolves, from four Wolf packs, were fitted with GPS radiocollars in the Rocky Mountain foothills, near Grande Cache, Alberta (2000-2001). We found Wolves did not use the lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Forest harvesting can increase human access and change the amount and spatial distribution of habitats for Wolves and their prey. Wolf packs in our study area had a seven-fold difference in the amount of forest harvested within their territories (Kuzyk et al 2004). The Cutbank pack (n = 7-8) had 36% of the forest in their territory harvested whereas the Lynx Creek (n = 12-18) pack had 7% harvested.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Forest harvesting can increase human access and change the amount and spatial distribution of habitats for Wolves and their prey. Wolf packs in our study area had a seven-fold difference in the amount of forest harvested within their territories (Kuzyk et al 2004). The Cutbank pack (n = 7-8) had 36% of the forest in their territory harvested whereas the Lynx Creek (n = 12-18) pack had 7% harvested.…”
Section: Discussionmentioning
confidence: 85%
“…Landscapes in westcentral Alberta are facing increased pressures from forest harvesting and the energy sector (oil and gas). Forest harvesting may alter the movements and distribution of Wolves (Kuzyk et al 2004) and ungulates (Smith et al 2000), and in combination with linear corridors (roads, seismic lines) from oil and gas activities, can enhance human access to once remote areas and possibly increase human-caused Wolf mortality from shooting and trapping. Enhanced predation by Wolves, facilitated by landscape change such as increased travel efficiency on linear corridors (James and Stuart -Smith 2000) and associated increases in alternate prey populations (James et al 2004), is thought to be the primary factor for Caribou declines in Alberta (Edmonds 1988;McLoughlin et al 2003 …”
mentioning
confidence: 99%
“…The extensive, recent logging in the area (Smith et al 2000) could favour deer numbers, and thereby influence predation risk to Caribou. Wolves in this study area were found to use forest cutblocks proportionately more than unharvested forests, which may be a response to increased number of deer and other ungulates that are attracted to the young vegetation in the cutblocks (Kuzyk et al 2004). A greater understanding of the role of deer in this Wolf-prey system is required, as most of the forest in westcentral Alberta has been allocated for timber harvest.…”
Section: Discussionmentioning
confidence: 89%
“…It is hypothesized that Woodland Caribou spatially separate themselves from Moose to avoid predation by Wolves (Bergerud and Elliot 1986;Seip 1992). Wolves may alter their use of habitats in response to industrial development such as forest harvesting (Kuzyk et al 2004) and human infrastructure such as roads and trails can enhance Wolf movements (Formozov 1946;Thurber et al 1994;Ciucci et al 2003). James (1999) reported that Wolves in winter travelled 2.8 times faster on a linear corridor than in the forest.…”
mentioning
confidence: 99%
“…In advance of developing RSF models for wolves, we assembled Geographic Information Systems (GIS) layers of landscape characteristics ( Table 2.1) that we hypothesized would influence wolf selection based on previous wolf-selection studies (Arjo and Pletscher 2004, Kuzyk et al 2004, Oakleaf et al 2006, Milakovic et al 2011. We classified the landscape into vegetation classes using multispectral images from SPOT 4/5 satellites (available at www.geobase.ca).…”
Section: Selection Of Landscape Features By Wolvesmentioning
confidence: 99%